Acute Cardiometabolic Responses to Medicine Ball Interval Training in Children - FAIGENBAUM, AVERY D. (Int J Exerc Sci, 2018)
Medicine ball interval training (MBIT) has been found to be an effective exercise modality in fitness programs, yet the acute physiological responses to this type of this exercise in youth are unknown. The purpose of this study was to examine the acute cardiometabolic responses to MBIT in children. Fourteen children (mean age 10.1 ± 1.3 yr) were tested for peak oxygen uptake (VO(2)peak) on a treadmill and subsequently (> 48 hours later) performed a progressive 10 min MBIT protocol of 5 exercises (EX): standing marches (EX1), alternating lunges (EX2), squat swings (EX3), chest passes (EX4) and double arm slams (EX5). A 2.3 kg medicine ball was used for all trials and each exercise was performed twice for 30 sec with a 30 sec rest interval between sets and exercises. Participants exercised while connected to a metabolic system and heart rate (HR) monitor. During the MBIT protocol, mean HR significantly (p<0.05, η(2) = 0.89) increased from 121.5 ± 12.3 bpm during EX1 to 178.3 ± 9.4 bpm during EX5 and mean VO(2) significantly (p<0.05, η(2)= 0.88) increased from 15.5 ± 2.9 ml × kg(−1) × min(−1) during EX1 to 34.9 ± 5.1 ml × kg(−1) × min(−1)during EX5. Mean HR and VO(2) values during MBIT ranged from 61.1% to 89.6% of HRpeak and from 28.2% to 63.5% of VO(2)peak. These descriptive data indicate that MBIT can pose a moderate to vigorous cardiometabolic stimulus in children.